Nodular acne infantum in a child treated with gonadorelin. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2020)
Neonatal acne (NA) is frequent in the first month of life and self-healing. Acne infantum (AI) is rare, occurs in the first 2 years of life, never in the first 3 months, is more localized than in adolescents, usually affecting only the cheeks, presents all the lesions of acne vulgaris, from comedones to nodules and cysts, persists for years and can leave scars before puberty (1). NA and AI are linked to paraphysiological adrenal and in the male genital stimulation, exceptionally to virilizing tumors or adrenal hyperplasia. Therefore, appropriate investigations are necessary only when AI arises between 5 and 8 years or is associated with signs of virilization such as hirsutism and premature closure of the epiphyses. We have not found in the literature cases of AI related to gonadorelin, which is agonist of gonadotropin releasing hormone. The latter can anyway be responsible for acne in adults (2).